Pengaruh Disclosure dan Opini Audit Tahun Sebelumnya terhadap Penerimaan Opini Going Concern pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Yunita Udin; Sufiati (Insan Cita Bongaya Research Journal, 2023)
This study aims to analyze the effect of disclosure and audit opinion of the previous year on the receipt of going concern audit opinion. Data collection using secondary data obtained from www.idx.co.id using purposive sampling techniques. The population is manufacturing companies listed on the Indonesia Stock Exchange totaling 150 companies, while the sample obtained amounted to 35 companies with observational data from 1 year of observation. The data analysis method uses logistic regression analysis techniques. The results showed that disclosure had a significant negative effect and the previous year's audit opinion had a significant positive effect on the going concern opinion